PERSONALITY DEVELOPMENTAL ISSUES IN CHILDREN AND ADOLESCENTS DURING WAR AND MILITARY ATTACKS: A LITERATURE REVIEW - Nasirova, Nigar (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . According to UNICEF, 473 million children currently live in countries affected by war or violent conflicts. Many children are forced to flee their towns or countries in search of safety, with numerous cases involving prolonged displacement or permanent loss of home. Some become orphans or are separated from their parents and caregivers. War functions as a large-scale disaster for both individuals and societies, and is associated with a range of negative emotions such as fear, anxiety, panic, and chaos. It therefore has a direct impact on mental health. War and its ongoing consequences lead to death, injury, disease, hunger, disruption of daily routines, separation from home, work, school, or neighbourhoods, as well as severe economic hardship, all of which contribute to feelings of helplessness and vulnerability. The traumatic effects of war trigger both physical and psychological problems and often undermine core moral values. In other words, these experiences may have longterm adverse effects on individuals’ futures. Children and adolescents are among the most vulnerable populations affected by mental health problems during wartime attacks. Therefore, the main objective of this study is to examine this issue through a review of the scientific literature. The goal is to analyse the principal directions of international research and identify key psychological challenges faced by children and adolescents in wartime conditions, based on a review of foreign publications focused predominantly on youth affected by armed conflict. M e t h o d s . The study was conducted using the method of comparative critique through a systematic literature review. R e s u l t s . Children and adolescents represent highly vulnerable groups during war and armed conflicts. Shortages of clean water and food, physical torture, captivity, bodily injuries, attacks, witnessing killings and wounds, torture and rape, as well as the direct exposure to shelling and explosions – these are just some of the traumatic experiences children may endure during war. The exposure to violence is the most common source of stress for children during armed conflict. However, children can also become perpetrators of violence, such as child soldiers or suicide bombers. Violence against children, separation from caregivers, and exposure to military attacks all lead to elevated levels of anxiety, post-traumatic stress disorder (PTSD), acute stress reactions, and increase the risk of long-term developmental and mental health problems. C o n c l u s i o n s . Based on numerous studies, the developmental and mental health problems most frequently observed among children in war and conflict settings include: anxiety, depression, sleep disorders, suicidal ideation, PTSD, tremors, dizziness, persistent fears, intrusive traumatic memories, anger, emotional distress, hopelessness, somatic symptoms associated with stress and psychological trauma (e.g., migraines, nausea, stomach problems), as well as interpersonal and marital instability, substance abuse, and violent behaviour.